Systemic Organization of Professional Competence, Creativity and Innovative Activity of A Future Kindergartener - Soliyev Ilhomjon Sobirjonovich; Boymirzayeva Shakhnoza Olimjon kizi (Zien Journals, 2023)
This article will be useful to methodologists, senior educators and educators of preschool educational institutions. It describes a system of methodological work to improve the quality of preschool education through increasing the professional competence of the teacher.
Keywords: preschool education; teacher; competence